Det muslimske brorskap i Egypten - Blichfeldt, Jan-Olaf (Religionsvidenskabeligt Tidsskrift, 1983)
When, after the first World War, the Association of Muslim Brothers was formed, it soon established itself as the largest movement among the political Islamic groups in the country. Hasan al-Banna, originally a teacher, founded the Association in Ismailia as a religious society in 1928. In 1939, however, the Brotherhood came to be a political organization, and began to participate in various political campaigns. Having as one of their main tenets that everything foreign to the recognized teachings of Islam ought to be abandoned, the brothers fought the British role in Egypt as well as the Jewish settlements in Palestine. Up to the revolution of the 23rd of July, 1952, their political activity increased considerably, conspiring at the same time with both the regime and its opponents. In 1954 the new government decided to dissolve the Brotherhood, and during the next twenty years, they were intensively harassed and out in jail. From the mid-seventies the Brothers began to be released and were even permitted to resume their activities as a religious society.’ Both during the time of Hasan al-Banna and in recent years the political confrontation between the Brotherhood and the regime has frequently been characterized by a well-founded literary propagandism. That is, various kinds of books, magazines and pamphlets which in a politically exaggerated form either defend the existing regime or oppose it. As to the former, it is – in addition to the more ordinary presentation of the government’s political positions and future plans – very much occupied with defining the concept of practical Islam by emphasizing its cultural achievements of the past while at the same time limiting its present role to be basically individual and spiritual. Reversibly, the opposition literature is agitating by means of claiming various political implementation of Islam. It has two basic approaches. There is the more direct mode where arguments of rejection, mocking and damnation are propagated by comparing the day-to-day political events with ideal Islam. Then there is the more indirect kind, which compares the contemporary situation with the hardship and suppression which, according to the Islamic Tradition, are one of the signs that the final battle against evil accompanied by the Last Judgement, is immanent. More significant, however, is the fact that this trend of spreading agitative literature seems to indicate the kind of adapted political profilation which the Muslim Brotherhood has sought to establish, defining itself both as a legitimate and oppositional movement between the government on the one side, and the remaining activist groups, such as Takfir al-hidjra, on the other.